If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4(4a + 9) + 6 = 0 Reorder the terms: 4(9 + 4a) + 6 = 0 (9 * 4 + 4a * 4) + 6 = 0 (36 + 16a) + 6 = 0 Reorder the terms: 36 + 6 + 16a = 0 Combine like terms: 36 + 6 = 42 42 + 16a = 0 Solving 42 + 16a = 0 Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '-42' to each side of the equation. 42 + -42 + 16a = 0 + -42 Combine like terms: 42 + -42 = 0 0 + 16a = 0 + -42 16a = 0 + -42 Combine like terms: 0 + -42 = -42 16a = -42 Divide each side by '16'. a = -2.625 Simplifying a = -2.625
| 5time-29=6 | | -47-6x+x=84 | | F(x)=x^2+x+.25 | | x(-4)=265 | | 3x^2+5x=291 | | -4(9z-8)= | | 4-(x+14)=3x-2 | | n/20=20 | | 8(c+2)= | | (x+1)(x+1)=-19 | | 10x^4-9x^2y-9y^2=0 | | X=-3/2y^2 | | b/3=27 | | -7x-y=23 | | 6/7÷2 | | x^2-50x+125=0 | | 4x-7=16-69 | | 9x+3-8x+8=24 | | n/16=1 | | -4x+3=-7x+15 | | y=2sin(4x)+3 | | 4x+3x=13+19 | | -7(6k-4)-7k= | | 88000+20x=30x | | (6x^2+7x-5)-(3x^2+2x-7)= | | 0=4x^3+2x-5 | | 5(3w)= | | 5x+x=4x-7 | | -12+7x^2=0 | | 14a-13=11a+2 | | 10x-20=-20x | | 20a+17=13a-18 |